Methylome and transcriptome joint analyses identify differentially expressed genes based on purebred and crossbred Tianjin-monkey Chicken - Shuli Xia; Guohui Li; Xianghua Zhao; Chenghao Zhou; Haitao Yu; Wei Han (Animal Biotechnology, 2024)
Tianjin-monkey Chicken is a locally bred naked neck poultry with limited population size. Herein, we intended to identify potential breed-related genes based on methylome and transcriptome analyses. Tianjin-monkey Chicken and Hy-line Brown Chicken were crossbred and the individuals were divided into three groups: PN (Purebred naked neck chicken(Tianjin-monkey Chicken)) group (n = 10); CN (Crossbred naked neck chicken) group (n = 10); CF (Crossbred feathered chicken) group (n = 10). These 30 individuals were subjected to whole genome bisulfite sequencing (WGBS) and transcriptome sequencing. Differential methylated regions were detected by WGBS. No significant difference existed in naked-neck-related traits between PN and CN chicken. CpG methylation level of the promoter region differed in PN, CN vs. CF chicken. By integrating methylome and transcriptome results, four genes were identified between PN and CN groups, and 24 key genes were identified between CN and CF groups, with great potential in breeding. The 24 genes were enriched on 32 GO terms and 3 KEGG pathways, such as ion transport. The promoter region CpG methylation level was distinct between feathered and naked neck groups. We identified 24 potential genes for future breeding, valuable for targeted breeding and genetic enhancement in poultry production.